69.7k views
3 votes
Somebody plz help me solve!!

Somebody plz help me solve!!-example-1

2 Answers

0 votes

Answer:

C) x = 3

Explanation:

factor out a 2 to get:

2(x² - 6x + 9) = 0

(x-3)² = 0

x = 3

User Amirouche
by
4.2k points
5 votes

Answer and Step-by-step explanation:

First, to find the zeros of the function, we can take out a common factor from the equation, and then factor.

The equation has a common factor of 2 (so distribute of the 2 from all of the numbers).

2(
x^2 - 6x + 9)

Now, we factor. Find two numbers that multiplies to
9x^2 and adds up to -6x.

-3x and -3x.

Now, we substitute these two for -6x.


2(x^2 - 3x-3x+9)

Factor.


2(x - 3)(x-3)

Finally, we set all of the values to 0 and solve for x.

2 ≠ 0

x - 3 = 0 x = 3

x - 3 = 0 x = 3

That means the answer is C. x = 3

(Not shown, but the multiplicity of this x value is 2, because there are two

x = 3)

#teamtrees #PAW (Plant And Water)

User Enrica
by
4.7k points